Human peripheral blood basophils primed by IL-3 produce IL-4 in response to IgE receptor stimulation - Brunner, Thomas; Heusser, Christoph; Dahinden, Clemens (My University, 1993)
In contrast to most cytokines, interleukin 4 (IL-4) expression is restricted to T lymphocytes, with the exception of mast cell lines and mast cells, as more recently demonstrated in rodents. Little is known, however, about the capacity of human nonlymphoid cells to produce IL-4. In this study we show that mature human basophils are capable of expressing IL-4 and examine the regulation of IL-4 production in comparison with the lipid mediator leukotriene C4. IL-4 was produced upon immunoglobulin E receptor (IgER) activation of basophils cultured with IL-3, a cytokine previously shown to prime these cells for enhanced release of inflammatory mediators. In some experiments, IL-3 or IgER activation alone also induced IL-4 production close to the detection limit. The effect of IL-3 on IgER-dependent IL-4 expression was dose and time dependent: maximal IL-4 production occurred between 18 and 48 h preexposure of basophils to 3-10 ng/ml IL-3. IgER-induced IL-4 synthesis and release by basophils cultured with IL-3 was rapid and complete after 6 h. In contrast to IL-3, other cytokines (IL-5, granulocyte/macrophage colony-stimulating factor, and nerve growth factor) that also prime basophils for enhanced histamine and leukotriene C4 release did not promote IgER-induced IL-4 synthesis. Basophils appear to secrete a "TH2-like" cytokine profile since no detectable IL-2 or interferon gamma was produced upon IgER activation. Mononuclear cells (depleted of basophils), cultured in parallel, did not release IL-4 in response to IL-3 and/or IgER activation, and produced approximately ten times less IL-4 than basophils upon nonspecific activation by phorbol ester and calcium ionophore. Thus, human basophils are an important cellular source of IL-4, and may, therefore, in addition to their inflammatory effector functions, also regulate the differentiation of T helper cells and B cells, in particular in allergic diseases.
Keywords: 570